Factors Associated with Delayed 2-Month Sputum Smear Conversion in MDR-TB Patients Treated with All-Oral Regimen at Persahabatan Hospital - Sitinjak, Sahat Anugerah Immanuel; Harfiani, Erna; Tjang, Yanto Sandy; Muktamiroh, Hikmah; Sutarto, Riyadi (Indonesian Society of Respirology (ISR), 2025)
Background: The emergence of multidrug-resistant tuberculosis (MDR-TB) presents significant challenges in achieving treatment success. Sputum conversion time, an essential indicator of treatment progress, varies among patients and may be influenced by demographic and clinical factors. This study aimed to identify factors associated with sputum conversion time in MDR-TB patients treated with all-oral regimens at Persahabatan Hospital during the 2021–2022 period. Method: This retrospective cohort study analyzed data from 154 MDR-TB patients treated with all-oral regimens at Persahabatan Hospital. Patients were categorized by sputum conversion time (≤2 months or >2 months). Independent variables included age, sex, diabetes mellitus, anemia, previous TB treatment, pulmonary cavitation, education level, marital status, and initial sputum AFB results. Inclusion criteria were primary pulmonary MDR-TB patients confirmed via sputum culture, aged ≥20 years, and treated per Indonesian national guidelines. Logistic regression analyses identified significant factors. Results: Among the nine factors studied, four significantly influenced sputum conversion time: elderly age, anemia, pulmonary cavitation, and initial sputum AFB results. Older age (≥60 years) was protective against delayed conversion, while anemia, pulmonary cavitation, and higher initial sputum AFB results were associated with prolonged conversion times. Conclusion: Factors such as anemia, pulmonary cavitation, and initial sputum results are associated with delayed sputum conversion, with elderly age as a protective factor against delayed sputum conversion.